2013
DOI: 10.1080/10503307.2013.838656
|View full text |Cite
|
Sign up to set email alerts
|

Integrating psychotherapy research with public health and public policy goals for incarcerated women and other vulnerable populations

Abstract: In this article, I review my research applying interpersonal treatments and interpersonal principles from psychotherapy for major depression and substance use to broader public health goals for incarcerated women and other vulnerable populations. A public health focus has led me to expand the boundaries of psychotherapy research to include partners such as prisons, parole officers, and bachelor's level providers; behaviors like risky sex; service delivery challenges; and ultimately to research with an eye towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
5
0
1
Order By: Relevance
“…Moreover, POR findings have demonstrated that feedback on progress (as well as the provision of related clinical tools) can significantly reduce the rate of deterioration in psychotherapy (Boswell et al, 2014;Lambert, 2010). While it remains to be seen if it is beneficial across diagnostic groups and settings (e.g., Johnson, 2014), outcome feedback is providing tools for clinicians to meet their most important ethical responsibility, "first do no harm." Outcome monitoring and feedback can also improve the cost effectiveness of psychotherapy; when therapists are receiving feedback on therapeutic change, patients who show early improvement have shorter treatment durations than those who do not (Strauss et al, 2014).…”
Section: Improving Clients' Outcomementioning
confidence: 96%
“…Moreover, POR findings have demonstrated that feedback on progress (as well as the provision of related clinical tools) can significantly reduce the rate of deterioration in psychotherapy (Boswell et al, 2014;Lambert, 2010). While it remains to be seen if it is beneficial across diagnostic groups and settings (e.g., Johnson, 2014), outcome feedback is providing tools for clinicians to meet their most important ethical responsibility, "first do no harm." Outcome monitoring and feedback can also improve the cost effectiveness of psychotherapy; when therapists are receiving feedback on therapeutic change, patients who show early improvement have shorter treatment durations than those who do not (Strauss et al, 2014).…”
Section: Improving Clients' Outcomementioning
confidence: 96%
“…Findings suggest that aspects of social support (e.g., strength of support, size of network, percentage and level of contact with substance users) are malleable factors that may be amenable to change while women are incarcerated and post-release while the type of support provided (e.g., overall support and/or disapproval of substance use and support for treatment) did not shift substantially over the course of the study. Future research, including following women for a longer period of time after re-entry, would help inform what social support changes may be maintained as well as which structural interventions (e.g., housing, employment, medical insurance, transportation) may increase women’s ability to sustain these positive changes (Johnson et al, in press). These findings also highlight the need for continued research to better understand how to building and maintaining healthy social supports can buffer against the multiple stressors (e.g., housing, job, caring for children, stigma) and improve outcomes for MDD-SUD women who are at high-risk for adverse substance use, mental health, and re-incarceration, following community reentry.…”
Section: Discussionmentioning
confidence: 99%
“…However, this advice fails to account for the environmental, economic and social context that have shaped these women’s lives and the world that they return to after prison release. For example, women face women significant structural and social barriers, such as poverty, discrimination, homelessness, histories of trauma and abuse, unemployment, limited education, limited treatment options, dependence on drug-using or abusive partner for shelter, economic support, or transportation to legally mandated treatment and other visits, and sometimes families and friendship networks in which there are no non-using members (Richie 2001; Kellett & Willging 2011; Johnson et al in press; Johnson in press). These factors limit women’s support network options after release (Kellett & Willging 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This modification was crucial, as most relapse occurs immediately following release from prison. A feasibility trial showed significant reductions in depression and substance abuse from baseline (in prison) to the end of the study (3 months post-release) (Johnson, Williams, & Zlotnick, in press). …”
Section: Other Hybrid Ipt Treatmentsmentioning
confidence: 99%